A cost–benefit analysis of the production system with improved and climate-resilient sorghum varieties in southern Mali - Coulibaly, Adama B.; Badolo, Félix; Yila, Jummai O.; Koné, Bourema; Nebié, Baloua; Worou, Nadine; Jumbo, Macdonald Bright; Savadogo, Kimseyinga (Frontiers in Climate, 2025)
Given the persistently low adoption rate of improved sorghum varieties over decades, it is relevant to assess whether it is profitable or not to grow these varieties in Mali. Over the past years, little evidence has demonstrated the profitability analysis as decision-support information regarding the adoption of improved sorghum varieties. This study used cost-benefit analysis to assess the profitability of two Improved and Climate-Resilient Sorghum Varieties (ICRSVs), “Soubatimi and Tiandougou-coura” compared to the “Local” ones, using three years of average yield data (2017, 2018, and 2020) in Sikasso region, Mali. The objective was to perform a consistent cost-benefit analysis through net income, cost-benefit ratio, and gross profit margin. The study used a farm partial budget framework, sensitivity analysis, and stochastic dominance analysis methods. A final sample of 31 farmers’ on-farm trials under the fertiliser package of “100 kg complex cereal and 50 kg urea” per hectare was held as the agronomic package. The key findings showed that both varieties were profitable, with 79,661 CFA (123.56 USD) and 45,073 CFA (69.91 USD) average net incomes corresponding to 1.54 and 1.32 CBR, and 34 and 24 percents average gross profit margins, respectively, while growing the “local” varieties was not profitable, with an average loss of 12,113 CFA (18.79 USD) with 0.91 CBR and 10 percent average gross profit margin. In light of these results, the study suggests a large dissemination of the ICRSVs in Mali. Policy-makers should facilitate the implementation of outreach programs to inform smallholder sorghum farmers on the ICRSVs’ traits and profitability information as decision support tool for a larger adoption.